2011
DOI: 10.1063/1.3615702
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Delamination Of Through Silicon Via Structures

Abstract: Articles you may be interested inMicro-Raman spectroscopy and analysis of near-surface stresses in silicon around through-silicon vias for threedimensional interconnects J. Appl. Phys. 111, 063513 (2012); 10.1063/1.3696980Micro-scale measurement and modeling of stress in silicon surrounding a tungsten-filled through-silicon via J. Appl. Phys. 110, 073517 (2011) Abstract. Continuous scaling of on-chip wiring structures has brought significant challenges for materials and processes beyond the 32 nm technology no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
6
1
Order By: Relevance
“…9a). A previous study has suggested that via extrusion could be caused by interfacial delamination [19]. However, in the present study, no evidence of interfacial delamination was observed.…”
Section: Effect Of Cu Plasticity On Via Extrusioncontrasting
confidence: 83%
“…9a). A previous study has suggested that via extrusion could be caused by interfacial delamination [19]. However, in the present study, no evidence of interfacial delamination was observed.…”
Section: Effect Of Cu Plasticity On Via Extrusioncontrasting
confidence: 83%
“…Sukharev [ 43 ] and Lau [ 44 ] reported finite element analysis simulations of TSV upon electromigration (EM) failure, which is when the TSV is unable to deliver the necessary voltage to any circuitry gate. Ryu et al [ 45 ] and Stiebing et al [ 46 ] suggested considering thermal cycling, which causes the TSV to extrude from the surrounding matrix or substrate. This phenomenon occurs due to a coefficient of thermal expansion mismatch between the surrounding substrate and the metal filler in TSV.…”
Section: Three-dimensional Integrated Circuits: the Technologymentioning
confidence: 99%
“…The vias have structures that go through the entire substrate and the stresses can be higher in the middle of the stack than the flanges. The stress field induced by differential thermal expansion in the via is threedimensional in nature [1]. It is necessary to investigate the stresses in the stacked via to get the full picture.…”
Section: Stacked Microvia Stressesmentioning
confidence: 99%